Identifikasi Musa Paradisiaca Dan Musa X Paradisiaca - Wijaya, Siti Saodatul; Sopiah, Siti; Supriatna, Ateng (Jurnal Ilmu Pertanian dan Perkebunan, 2023)
Musa paradisiaca and Musa x paradisiaca are two common banana species found worldwide. Banana is a fruit plant that comes from the Musaceae family and is an important staple food in many countries. Musa paradisiaca, which is also known as plantain banana, is a species of banana that is consumed ripe or after cooking. These bananas are generally larger and stiffer than other banana varieties. Musa paradisiaca has a richer taste and is usually used in dishes or preparations such as fried bananas. Musa x paradisiaca is a hybrid between Musa paradisiaca and other banana species, such as Musa acuminata or Musa balbisiana. This hybrid is commonly known as banana kepok or plantain. Musa x paradisiaca has a larger size than regular bananas and is usually consumed ripe. It tastes sweet and delicious, and is often used for direct consumption or in the preparation of desserts. The method we use is observation, where we directly observe Kp. Jadaria, Rt.02 Rw.05. Cibiu Wetan Village.